A case-control study to evaluate risk factors for ectopic pregnancy - Khedar, Sangita; Mital, Premlata; Rajoria, Lata; Gupta, Divya; Shekhawat, Usha; Singhal, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Morbidity and mortality associated with ectopic pregnancy are directly related to the length of time required for diagnosis. Knowledge of risk factors for ectopic pregnancy will help an obstetrician to suspect and diagnose the condition early. Therefore, the present study was designed to identify potential risk factors and to evaluate the contribution of the risk factors in ectopic pregnancy. Methods: Study population consists of 65 women with ectopic pregnancy and for each ectopic case one woman with first trimester intrauterine pregnancy was recruited as control. Data were retrieved from all through a structured proforma. Data were analyzed statistically. Results: Various significant risk factors for ectopic pregnancy found were pelvic inflammatory disease, tubal ligation, age above 30 yrs, previous use of IUCD, low socio-economic status, tubal infertility and genital tuberculosis while no significant association was seen with smoking, age below 30 years, history of prior induced abortion, oral contraceptive pills and clomiphene citrate. Conclusions: Increase awareness and knowledge of risk factors will help obstetricians to suspect and diagnose ectopic pregnancy early and accurately and enable them to plan medical treatment. Surgical treatment will be reserved for ruptured ectopic pregnancy and haemodynamically unstable patients.